Faith-Inspired Schools in Sub-Saharan Africa : An Introduction to the Summer 2014 Issue - Wodon, Quentin (Taylor and Francis, 2014)
At a time when many sub-Saharan African countries may not achieve the education targets set forth in the Millennium Development Goals, and discussions on the post-2015 agenda are the topic of the day in development circles, the contribution of private providers of education, including faith-inspired schools (FISs), is crucial. For these providers to work alongside the state in the delivery of services, and possibly benefit from state support, basic information is required on their market share, reach to the poor, cost for households, and satisfaction of users with the services received. Yet today little systematic evidence is available on the role of FISs, at least in sub-Saharan Africa, and how they compare to other (public and private secular) schools. This special issue of The Review of Faith & International Affairs aims to bridge this knowledge gap. The purpose of this introduction is to briefly summarize the articles’ main findings and suggest some areas for further research.